2019
DOI: 10.1097/txd.0000000000000958
|View full text |Cite
|
Sign up to set email alerts
|

Renal Arteriovenous Fistula in a Renal Transplant Recipient: A Case Report and Literature Review

Abstract: Background. Renal arteriovenous fistula (rAVF) is a rare complication after a total nephrectomy, with only 72 cases reported in the last literature review published in 1997. AVF has never been described in a renal transplant recipient, and the possible consequences of hemodetournement on the graft function are unknown. Methods. We hereby reported the first case of rAVF occurring in a renal transplant recipient and analyzed all cases of postnephrectomy r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…6,7 The most recently published literature review reported another twenty-one cases between 1997 and 2019. 4 The reported incidence of renal artery arteriovenous fistula accompanying pseudoaneurysm is less than 1%. 8 This case report adds to the published literature on this rare entity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 The most recently published literature review reported another twenty-one cases between 1997 and 2019. 4 The reported incidence of renal artery arteriovenous fistula accompanying pseudoaneurysm is less than 1%. 8 This case report adds to the published literature on this rare entity.…”
Section: Discussionmentioning
confidence: 99%
“…A well-documented risk factor for renal arteriovenous fistulae following nephrectomy is mass ligation of the renal pedicle. 3-5…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation